Resultados e implicações do processo de adaptação de próteses auditivas em usuários atendidos em uma instituição pública federal - Freitas, Carine Dias de (2006)
According to Ministério da Saúde is there the necessity to survey of the Country situation in relation to the hearing impairment, between the many aspects it is the hearing aid supply and the results after the act of receiving it, what it would make possible an improvement of the actions planning in Auditory Health Attention. Some research have been carried through with hearing aid users, meantime in the specialized literature, studies related with fitted users saw in the Sistema Único de Saúde, had not been found. Thus being, this study has like aims: to verify the difficulties related to the use and battery manipulation and ear molds and to the characteristics of the amplification in this group of study; and to compare the intervention results from self-assessment questionnaires in patients with and without related complaints with the characteristics of the amplification. In this way, the study consisted of individuals with symmetrical bilaterally hearing losses, sensorineural or mixed, from moderate to moderately severe degrees, between 12 and 77 years age, all hearing aid users of digital or hibrid for a minimum period of three months. Initially, it was carried through an interview with topics related to the experience and the use and battery manipulation, ear molds and hearing aids in the 31 individuals of the study. After, they had been applied in 25 individuals, the evaluations with self-assessment questionnaires HHIE-S (Hearing Handicap Inventory will be the Elderly Screening Version) or HHIA (Hearing Handicap Inventory will be Adult) and APHAB (Abbreviated Profile of Hearing Aid Benefit), which had allowed to verify the difficulties tried in the daily life communication situations in individuals without (Group 1) and with complaints related to the amplification characteristics (Group 2). Of the 31 interviewed individuals, 21 users had presented some kind of complaint related to hearing aids characteristics. Already in relation to the evaluations with self-assessment qestionnaires, applied in 25 of them, there was not found significant difference statistical among the studied groups in relation to questionnaires HHIE-S and HHIA, and about the APHAB significant difference statistical only in communication favorable situations of was evidenced, having Group 1 gotten benefit better. In HHIE-S and HHIA, the means values of hearing handicap was 34,71% for Group 1 and 45,82% for Group 2, indicating a bigger perception for the group with complaints. The values of benefit in the APHAB for Group 1 was 68,62% (FC), 37,12% (RA), 48,38 (RV) and -9,25 (AS) and in Group 2, it verified 39,59% (FC), 38,12% (RA), 39,88% (RV) and -28,18% (AS), evidencing a significant reduction of the hearing disabilities with the use of the hearing aids in communication favorable situations (FC), in reverberant environments (RV) and in the ambient noise presence (RA) for both groups. In negative situations of perception of the ambient sounds (AS), the performance with the use of the hearing aid was worse for both groups, confirmed for the negative values of benefit. Finnaly, the critical appreciation of the results allowed to conclude that 12.90%, 58,06% and 67,74% of the interviewed individuals (N=31) had presented difficulties related to the battery, to the ear molds or capsules and to the amplification characteristics, respectively; and significant differences between the groups studied (N=25) in the HHIE-S and HHIA protocols, as well as in the APHAB had not been found, except in sub-scale favorable communication situations, where Group 1 (without complaints) got benefit better.